Image World : Art and Media Culture - Heiferman, Marvin; Phillips, Lisa; Hanhardt, John G. (New York : Whitney Museum of American Art, 1989)
Acconci, Vito ; Adams, Dennis ; Anderson, Laurie ; Baldessari, John ; Beckley, William ; Bender, Gretchen ; Berman, Wallace ; Bickerton, Ashley ; Birnbaum, Dara ; Blake, Nayland ; Bloom, Barbara ; Brauntuch, Troy ; etc.
Image World : Art and Media Culture, Whitney Museum of American Art, New York, November 8, 1989 - February 18, 1990 ; Public Projects, November 22 - December 31, 1989
boek